Prevalence of polycystic ovary syndrome (PCOS) among reproductive age women from Kashmir valley: A cross‐sectional study. Issue 2 (20th March 2020) - Ganie, Mohd Ashraf; Rashid, Aafia; Sahu, Danendra; Nisar, Sobia; Wani, Ishfaq A.; Khan, Junaida
Abstract: Objective: To estimate the prevalence of polycystic ovary syndrome (PCOS) among women of reproductive age across educational institutions in the Kashmir valley. Methods: A cross‐sectional study was conducted from May 2013 to May 2015. Eligible girls and women aged 15–40 years were included using a multistage random selection process from five out of 12 districts in turn housing 14 educational institutions. They were screened through a brief questionnaire in a staged manner. After obtaining consent, women underwent detailed clinical, biochemical, hormonal, and sonographic evaluation to satisfy Rotterdam 2003 criteria. The participants were also evaluated using NIH and AE‐PCOS criteria. Results: Out of a total of 3300 eligible women, 964 women were evaluated using a structured questionnaire. Among these, 446 (46.4%) were identified as "probable PCOS" cases. Out of 171 probable PCOS women who completed all biochemical, hormonal, and sonographic assessment, 35.3% qualified for a diagnosis of PCOS using Rotterdam criteria. The prevalence of PCOS was 28.9% by NIH criteria and 34.3% by AE‐PCOS criteria. Conclusion: The prevalence of PCOS is high among Kashmiri women and is probably the highest in a published series globally. A countrywide systematic prevalence study is warranted to reconfirm the findings. Abstract : A high prevalence of PCOS was demonstrated among women in the Kashmir valley, thereby suggesting ethnic and environmental factors contributed to the pathogenesis of disease.